2008
DOI: 10.1007/978-3-540-85279-7_6
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Method for Reuse Potential Assessment in Reengineering-Based Product Line Adoption

Abstract: Software product lines are rarely developed from scratch. Instead the development of a product line by reengineering existing systems is a more common scenario, which relies on the collaboration of diverse stakeholders to lay its foundations. The paper describes a collaborative scoping approach for organizations migrating existing products to a product line. The approach uses established practices from the field of reengineering and architectural recovery and synthesizes them in a collaborative process. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is also important to extract features from existing products along with higher-level architectural information. Instead of a domain potential analysis, a reuse potential assessment of legacy assets needs to be conducted to reuse existing experience in a particular domain (Noor et al, 2007b). Legacy assets to be reengineered need to be identified and transformed into reusable components in a core asset base (referred to as reuse infrastructure scoping).…”
Section: Product Line Engineering and Product Line Planningmentioning
confidence: 99%
“…It is also important to extract features from existing products along with higher-level architectural information. Instead of a domain potential analysis, a reuse potential assessment of legacy assets needs to be conducted to reuse existing experience in a particular domain (Noor et al, 2007b). Legacy assets to be reengineered need to be identified and transformed into reusable components in a core asset base (referred to as reuse infrastructure scoping).…”
Section: Product Line Engineering and Product Line Planningmentioning
confidence: 99%
“…Noor describes two studies (Noor et al, 2006(Noor et al, , 2008, where the collaboration factor is alleviated through the collaboration engineering technique. This improves communication and collaboration between SPL stakeholders during the SPL SC.…”
Section: Related Workmentioning
confidence: 99%
“…Basically, the use of those patterns would address significant agile principles for the scoping and requirements disciplines such as (i) "Business people and developers must work together daily throughout the project" and (iii) "At regular intervals, the team reflects on how to become more effective, then tunes and adjusts its behavior accordingly" (Noor et al, 2008(Noor et al, , 2006.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Some suggestions include the Planning Game [3] from the XP methodology can increase agility in SPL organisations, particularly for gathering and negotiating the product requirements. The use of Agile practices during application engineering activities is suggested [2], in particular to perform product tailoring [9] and to support the collaborative working of stakeholders [1].…”
Section: Agile Practices and Splmentioning
confidence: 99%
“…We believe that any successful effort to introduce Agile practices in the product derivation process can make SPL significantly more effective and efficient. While some research in the area of Agile SPL has been reported [1][2][3][8][9][10], much of this has been related to identifying the opportunities and challenges. There has been little research conducted on the use of Agile approaches in the product derivation process while no Agile approach for product derivation have been developed.…”
Section: Introductionmentioning
confidence: 99%